The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1097/sla.0b013e31828c88fc
|View full text |Cite
|
Sign up to set email alerts
|

Operation Debrief

Abstract: SHARP is an effective and efficient means of improving performance feedback in the operating room. Its routine use should be promoted to optimize workplace-based learning and foster a positive culture of debriefing and performance improvement within surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(20 citation statements)
references
References 22 publications
(28 reference statements)
0
19
0
1
Order By: Relevance
“…Each student reviewed his or her video using a rubric ( Supplement 1 ) incorporating the SHARP debriefing tool [ 13 ]. The SHARP tool encourages students to identify aspects that they performed well, areas requiring improvement, whether the learning objectives for the task were met, and to outline a short plan for addressing the areas requiring improvement [ 13 ]. Students then uploaded the video and written assignment to the university learning management system for grading.…”
Section: Methodsmentioning
confidence: 99%
“…Each student reviewed his or her video using a rubric ( Supplement 1 ) incorporating the SHARP debriefing tool [ 13 ]. The SHARP tool encourages students to identify aspects that they performed well, areas requiring improvement, whether the learning objectives for the task were met, and to outline a short plan for addressing the areas requiring improvement [ 13 ]. Students then uploaded the video and written assignment to the university learning management system for grading.…”
Section: Methodsmentioning
confidence: 99%
“…It should also be borne in mind that in some circumstances or when delivered inappropriately, feedback may not be effective; for instance, although a number of studies in medical students have found feedback to improve acquisition of basic surgical skills, 8–10 some have failed to find this, 22 and the effect of feedback may plateau. 23 24 Frameworks have been suggested in order to ensure appropriate dissemination of feedback, 25 which is particularly important given the fact that trainees often feel they are provided with inadequate feedback despite senior surgeons feeling their feedback provision is adequate. 26 27 …”
Section: Discussionmentioning
confidence: 99%
“…Although Waznonis (2014) has identified 22 methods for debriefing, we have selected five commonly cited methods and two approaches to assess debriefings (Dieckmann, Reddersen, Zieger, & Rall, 2008;Rudolph, Simon, Raemer, & Eppich, 2008;Arora, Ahmed, Paige, Nestel, & Sevdalis, 2012;Brett-Fleegler, Rudolph, Eppich, Monuteaux, & Simon, 2012;Dreifuerst, 2012;Ahmed, Arora, Russ, Darzi, & Sevdalis, 2013;Phrampus & O'Donnell, 2013). For each method, we have aligned Gibbs's reflective cycle with the six stages (Table 1).…”
Section: Gibbs's Reflective Cycle and Its Relation To Debriefing Methodsmentioning
confidence: 99%
“…Some methods combine several of Gibbs's stages under one heading, whereas others extend specific stages. SHARP (Ahmed et al, 2013) does not include specific reference to either description or feelings. ''Meaningful debriefing'' (Dreifuerst, 2012) uses Gibbs's stages out of sequence with emphasis on analysis, whereas the Objective Structured Assessment of Debriefing (Arora et al, 2012) precisely mirrors the stages in Gibbs's reflective cycle.…”
Section: Gibbs's Reflective Cycle and Its Relation To Debriefing Methodsmentioning
confidence: 99%